Effect of hydrogen on plasticity of α-Fe: A multi-scale assessment. (June 2023) - Kumar, Pranav; Ludhwani, Mohit M.; Das, Sambit; Gavini, Vikram; Kanjarla, Anand; Adlakha, Ilaksh
Abstract: A multi-scale study was carried out to quantify the effect of interstitial hydrogen concentration on plasticity in α -Fe. In this work, the influence of hydrogen on the screw dislocation glide behavior was examined across several length-scales. The insights obtained were integrated to provide an accurate continuum description for the effect of hydrogen on the dislocation based plasticity in polycrystalline α -Fe. At the outset of this work, a new FeH interatomic potential was formulated that enhanced the atomistic estimation of the variation in dislocation glide behavior in presence of hydrogen. Next, the dislocation core reconstruction observed due to the addition of hydrogen using atomistic simulations was validated with the help of large-scale DFT calculations based on the DFT-FE framework. Several atomistic simulations were carried out to comprehensively quantify the effect of hydrogen on the non-Schmid behavior exhibited during the dislocation glide in α -Fe. Finally, crystal plasticity simulations were carried out to understand the effect of hydrogen on the meso-scale deformation behavior of polycrystalline α -Fe. Graphical abstract: Highlights: A novel multi-scale study to quantify the effect of hydrogen on plasticity in α -Fe. Developed a new FeH interatomic potential for modeling dislocation–hydrogen. Estimated the influence of hydrogen on atomistic plasticity. Hydrogen reduced the CRSS and decreased the T/AT asymmetry exhibited by the dislocation. At the meso-scale, the presence of hydrogen resulted in increased yield strength.